2013
DOI: 10.1371/journal.pone.0062482
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Enveloped Viruses Infectivity by Curcumin

Abstract: Curcumin, a natural compound and ingredient in curry, has antiinflammatory, antioxidant, and anticarcinogenic properties. Previously, we reported that curcumin abrogated influenza virus infectivity by inhibiting hemagglutination (HA) activity. This study demonstrates a novel mechanism by which curcumin inhibits the infectivity of enveloped viruses. In all analyzed enveloped viruses, including the influenza virus, curcumin inhibited plaque formation. In contrast, the nonenveloped enterovirus 71 remained unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 30 publications
(54 reference statements)
5
144
0
1
Order By: Relevance
“…Curcumin has been reported to inhibit type A influenza virus (IAV) infection by interfering with viral hemagglutination (HA) activity [54,55], whereas THC has been less effective for suppression of IAV infection [45]. Further studies indicated that curcumin, but not THC, harbors the HA inhibitory effect.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Curcumin has been reported to inhibit type A influenza virus (IAV) infection by interfering with viral hemagglutination (HA) activity [54,55], whereas THC has been less effective for suppression of IAV infection [45]. Further studies indicated that curcumin, but not THC, harbors the HA inhibitory effect.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Ou et al (2013) reported that the presence of the double bonds in the central seven-carbon chain enhances the curcumin-dependent anti-IAV activity and curcumin might interfere with IAV entry by its interaction with the receptor binding region of hemagglutinin. Chen et al (2013) also reported that curcumin can inhibit influenza virus by disrupting integrity of the viral envelope and liposomal membranes. However, it is not clear whether curcumin and its derivatives can inhibit neuraminidase of influenza virus.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous study demonstrated Cur acts as a novel agent to inactivate infectivity of the type A influenza viruses (IAV) via multiple mechanisms, such as the inhibition of viral haemagglutination (HA) function, and to affect envelop integrity [4,15]. Moreover, the anti-influenza activity of Cur and other two curcuminoids, DMC and BDMC, is indistinguishable, indicating that the methoxyl group on the phenyl rings was not the crucial portion contributing to the anti-IAV activity and the inhibition of viral HA function mediated by Cur [4].…”
Section: Introductionmentioning
confidence: 99%